Kemas ulang informasi pohon industri berbasis Google Sites di PDDI LIPI - Lidya Maretti (Jurnal Informatio, 2022)
Information repackaging is an information service that allows users to access information content more easily, quickly, anytime, and anywhere. This study aimed to explain the process of repackaging industrial tree information based on Google Sites at PDDI LIPI. This study used the literature study method by collecting relevant references and participatory observation. The study results showed that repackaging industrial tree information was an activity of repackaging information, changing sources of journal article information into other forms that were more suitable for users, namely website-based digital information. The industrial tree is an information package that aims to provide an overview of a particular topic with primary commodities and supporting commodities. The activity of the information repackaging process based on Google Sites consists of a series of stages starting from determining the primary commodity of information, searching or searching for information sources, information storage, information analysis, designing the structure or information scheme of commodity utilization, and ending with repackaging information using Google Sites. In conclusion, the author can describe a series of stages of the information repackaging process through the creation of a website-based industrial tree using Google Sites as a means of implementation, starting from 1) Needs analysis; 2) Determining user profiles, target audiences, packaging forms and make scheduling and costs; 3) Determine and identify the purpose of packaging information; 4) Selecting, selecting and determining library sources; 5) Determine the strategy for finding sources of information; 6) Determine the location of information and access to media use; 7) Industrial tree repackaging process; 8) Controlling and monitoring; 9) Establish an information packaging dissemination system; 10) Distribution of information packaging; 11) Reviews, and 12) Evaluation.